Analyzing sustainability of Chinese mining cities using an association rule mining approach. (September 2016) - Zeng, Lijun; Wang, Bingcheng; Fan, Liu; Wu, Jianguo
Abstract: Mining cities are of vital importance to the global development, but they are facing great challenges to achieve sustainability goals. Understanding the characteristics and patterns of the environmental, economic, and social conditions of mining cities is critical to promoting their sustainability. After developing an Indicator System for Mining City Sustainability, we collected data from 110 prefecture-level cities and analyzed environmental, economic, and social characteristics of these mining cities using a data-mining method – Association rule mining. Our analysis revealed some novel, implicit, and previously unknown characteristics and patterns of mining city sustainability in China. We found that education investment, economic development, and some aspects of society were substantially unbalanced in most Chinese mining cities. Most coal-mining cites had a larger proportion of mining population, and usually faced severe challenges in reducing industrial dust emission. The unsustainable characteristics of Chinese mining cities exhibited distinctive regional patterns and should be considered explicitly in policy making to promote the sustainability of these urban areas. Highlights: Most coal-mining cites have a larger proportion of mining population. Mining city sustainability in China presents distinctive regional characteristics. Southwest Chinese mining cities have a higher GDP growth rate with less air pollution. North Chinese mining cities have challenges in reducing industrial dust emissions.